Digital and Palmer Dermatoglyphic; A Bio-Indicator for Intelligence Quotient (Journal of Basic and Applied Research in Biomedicine, 2022)
Dermatoglyphic attributes once formed in the womb remains unique and persists throughout life for individuals until decomposition after death in the tombs. This research work aimed at finding the relative associations that exists between the dermatoglyphic parameters and intelligence level among the medical students of Bingham University, Karu Nigeria with ultimate purpose of using dermatoglyphic characteristics as bio-indicators for selection of categories of students into good, average and weak academic performances.  A total number of 65 medical students (30 male and 35 female students) who were in 3rd year were selected for this study, students were categorised according to their academic performances in the Anatomy courses into the good, average and weak at the end of the academic session. Dermatoglyphic printings including the finger and palm prints were taken using Indian ink method.  Ulnar loop pattern was prevalence in all categories of students (Right hand: good 72%, average 58%, weak 40%, Left hand: good 72%, average 50%, weak 51% ) and higher symmetrical arrangement was observed in both hands (right and left hands) among the good student, however, no incidence of arch pattern was recorded among the good set of students.  More than two different sets of patterns were observed to be distributed in each hand among the weak category of student and also asymmetrical arrangements were significant (P